Construction and Expression of Mouse-human Chimeric Antibody SZ-51 Specific for Activated Platelet P-selectin - Gu, Jianming; Liu, Yue; Xia, Lijun; Wan, Haiying; Li, Peixia; Zhang, Xiaomin; Ruan, Changgeng (Thrombosis and Haemostasis, 1997)
A murine monoclonal (mAb) SZ-51 specific for human P-selectin may be used for in vivo thrombus imaging and for the targeting of fibrinolytic agents to thrombi. In order to reduce the immunogenicity of the murine mAb SZ-51 in humans, we cloned and sequenced the cDNAs encoding the variable region of mAb SZ-51 in order to develop mouse/human chimeric reagents. The E. coli expression vector. pHENl-SZ51 Fab/Hu was constructed by fusing the variable regions of mAb SZ-51 with human IgG γICHI and Cκ genes. The constructs were introduced into E. coli HB2151 for expression of soluble chimeric Fab fragment. We also constructed two fusion products by joining the variable regions of mouse antibody to the appropriate constant regions of human Igγl and κ. These chimeras were cloned into two eukaryotic selectable expression vectors separately, which were then cotransfected into a non-Ig secreting murine myeloma line SP2/0 with lipofectin reagent. Six cell lines remained positive for Ig secretion. The highest producing cell line, which showed stable integration and expression at 5 mg/1 of culture, was selected for the large scale production of chimeric antibody. Immunoblotting analysis demonstrated that both of the chimeric antibodies (SZ51Fab/Hu, SZ51/Hu) in the culture supernatants, like the native mAb SZ-51, bind P-selectin. In addition, the whole chimeric antibody can compete for binding to activated platelets with murine SZ-51. Therefore, the SZ-51 chimeric antibody may be a potential agent for diagnosis and treatment of thrombotic diseases in the future.